Peran Guru Dalam Mengatasi Permasalahan Attention Deficit Hyperactive Disorder Terhadap Anak Usia Dini di RA AR-RIDHO - Jamilah, Nur Asy-Syifa; Wulandari, Hayani (Jurnal Ilmiah Wahana Pendidikan, 2024)
The teacher's role in dealing with hyperactive children is as a facilitator, planner and role model for students' learning, guiding and supporting students' academic progress as well as being a role model for students' behavior and work ethic. The aim of this research is to determine the role of teachers in overcoming the problem of Attention Deficit Hyperactive Disorder (ADHD) at RA Ar-Ridho. This research method uses a qualitative descriptive method. The data collection technique uses a questionnaire. The subjects of this research were 19 teachers. The results of this research show that 85% of the teacher's role can overcome the problems of Attention Deficit Hyperactive Disorder (ADHD) children.